Muslim Personal Law, Yes and No Religious Leader's Views on its Legalization - Suleman, Muhammed (2023)
Muslim personal law (MPL) has been a controversial issue in South Africa. Proponents of it becoming legalized in South Africa, say that women would be handed benefits which they do not have because their marriages lack legal recognition. Women lack support from theological bodies which are largely male dominated. These bodies have been accused of adopting a conservative view of Islam and of wanting to maintain the patriarchal status quo. It can be argued that such views are culturally and structurally violent, as they lead to direct violence, as women are denied important resources such as divorce which could be legally ratified in a court where MPL is recognized. Religious leaders who are against MPL, are in a state of "hysteresis" as Bourdieu would say. Theological bodies, on the other hand, state that MPL cannot be inter-twined with secular laws that are contrary to Shariah (Islamic law). They criticize the clergy who were in favor of MPL becoming legalized. My doctoral research focused on religious leaders' views of domestic violence experienced by Muslim women. Using a qualitative research methodology, their views were obtained, using in-depth interviews. Thereafter, their opinions were organized in the form of themes. One of the core themes that emerged from the data, was Muslim religious leaders' views on MPL. In conjunction with the literature, it was found that there are religious leaders against the legalization of MPL and those who favor MPL becoming legalized.
Keywords: Muslim religious leaders; Muslim personal law; cultural violence; Structural Violence; Habitus; Field; capitals